Implementasi Algoritma Convolutional Neural Network Dalam Mengklasifikasi Jenis Burung - Raihan Maulana; Raisya Dwi Zahra Putri; Sindy Fitriani Margareth Sihaloho; Sri Mulyana (Journal of Creative Student Research, 2023)
Birds are a group of vertebrate animals that have feathers and wings. There is a diversity of bird species in the world, that makes it difficult for ordinary people to distinguish certain types of birds, but technological advances now allow for easier identification. This research uses a dataset from Kaggle to classify various bird species in the world. This dataset consists of 84,635 bird images, covering 525 different species. In this study, we focused on 30 classes, with a total of 5,050 data divided into 4,760 training data, and 150 data each for test and validation. Classification was performed using a Convolutional Neural Network (CNN), with the training process yielding the highest accuracy of 96.30% on training data and 81.33% on validation data after 20 epochs.